Preparation method and application of composite electrode material

By using atomic layer deposition technology to deposit lithium iron phosphate on the surface of high-nickel ternary materials, the problems of poor thermal stability and coating uniformity are solved, and the electrochemical performance and cyclic stability of lithium-ion batteries are significantly improved.

CN119905506APending Publication Date: 2025-04-29ZHEJIANG ZEEKR INTELLIGENT TECH CO LTD +2

Patent Information

Application Number
CN202510004322.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-02
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The existing high-nickel ternary materials have problems such as poor thermal stability, serious gas production and low retention rates in lithium-ion batteries, and poor solid-phase coating uniformity affects electrochemical performance.

Method used

Atomic layer deposition technology is used to deposit lithium iron phosphate on the surface of high-nickel ternary materials to achieve atomic level uniform coating, enhancing the thermal stability and electrochemical properties of the material.

Benefits of technology

Through the atomic layer coating technology, the coating uniformity and thickness control are improved, the contact area between the material and the electrolyte is reduced, the adverse interface reaction is suppressed, and the electrochemical performance and cycle stability of lithium-ion batteries are significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119905506A_ABST
    Figure CN119905506A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a composite electrode material, and the method comprises the steps: mixing a hydroxide precursor, a lithium salt compound and a cosolvent, and carrying out the first sintering, crushing and grading, thereby obtaining a sintered material; mixing the sintered material with a surfactant, and performing secondary sintering and crushing to obtain the high-nickel ternary material, and putting the high-nickel ternary material into a reaction cavity of atomic layer deposition equipment, setting reaction conditions, introducing one or more sediments into the reaction cavity, and applying the reaction conditions to obtain the composite electrode material coated with lithium iron phosphate. The composite electrode material coated with the lithium iron phosphate is prepared by adopting the preparation method, the lithium iron phosphate is deposited on the surface of the composite electrode material, the composite electrode material is thin and uniform, the material interface is improved, meanwhile, the capacity can be provided, and the situation that the capacity is too much reduced due to existence of a coating object is avoided; and the long-term cycle performance is effectively improved by depositing a proper amount of lithium iron phosphate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of lithium-ion batteries, and in particular to a preparation method and application of a composite electrode material. Background Art

[0002] In recent years, as the heart of new energy vehicles, lithium-ion batteries have seen an increasing installed capacity year by year due to their high specific energy, long life and high safety. Among them, as the key material for providing energy for lithium-ion batteries, the optimization and improvement of positive electrode materials is urgent.

[0003] Ternary cathode materials (LiNi x CoyMn 1-x-y O2, 0<x, y<1) has become the main development direction of positive electrode materials for power batteries due to its high energy density and long cycle life, while high-nickel ternary materials (Ni≥0.8) have become a better choice for battery cell manufacturers due to their high energy density. With the increasing demand for energy density and safety of new energy vehicles, the main high-nickel ternary materials for power batteries on the market currently have poor thermal stability, severe gas production and low retention rate in long-term cycles.

[0004] In order to solve the above problems, researchers in the prior art have proposed to use a multi-element doping formula to improve the material's compressive resistance, reduce the degree of particle cracking, and improve the dynamic stability during the cycle, that is, to improve the material's capacity retention rate during the cycle; at the same time, a multi-element coating formula will be used to modify and optimize the material interface, reduce the damage of the electrolyte to the interface, and improve the capacity and capacity retention rate. However, the above-mentioned material modification process mostly uses solid-phase sintering, that is, by mixing solid powder with coating material, and then subjecting it to high-temperature treatment, the coating material is melted and coated on the surface of the electrode material. The coating uniformity and thickness are difficult to control. For example, solid-phase coating of Al2O3, although it achieves the effect of protecting the interface, the coating effect is uneven. The places where the coating is concentrated are not conducive to lithium ion transmission, which in turn affects the capacity. The places where the coating is insufficient do not play a role in protecting the interface.

[0005] Therefore, there is an urgent need to provide a preparation method and application of a composite electrode material to solve the above technical problems. Summary of the invention

[0006] The present application provides a preparation method and application of a composite electrode material to solve the problems of poor surface coating uniformity and poor long-term electrical performance of high-nickel materials in the prior art.

[0007] In a first aspect, the present application provides a method for preparing a composite electrode material, comprising the following steps:

[0008] S1: mixing a hydroxide precursor, a lithium salt compound and a solvent, and performing a first sintering, crushing and classification to obtain a sintering material;

[0009] S2: mixing the sintered material with a surfactant, and performing a second sintering and crushing to obtain a high-nickel ternary material;

[0010] S3 places the high-nickel ternary material into a reaction chamber of an atomic layer deposition device, sets reaction conditions for the reaction chamber, introduces one or more sediments into the reaction chamber and applies the reaction conditions to obtain a composite electrode material coated with lithium iron phosphate.

[0011] By adopting the above-mentioned technical scheme, lithium iron phosphate is deposited on the surface of high-nickel ternary material using atomic layer film technology to obtain a composite electrode material coated with lithium iron phosphate. On the one hand, the use of atomic layer film technology can achieve uniform coating at the atomic level, greatly improve the coating uniformity, and effectively solve the problem of poor solid phase coating uniformity; on the other hand, lithium iron phosphate as a coating layer reduces the contact area between the material and the electrolyte, slows down the corrosion of the electrolyte to the material during the cycle, inhibits the occurrence of adverse interfacial reactions, and effectively improves the electrochemical performance of lithium-ion batteries; at the same time, the coating layer can also reduce the contact area between the high-nickel ternary material and the air, effectively reducing the residual lithium in the material.

[0012] An optional solution is that in S1, the mass ratio of the lithium salt compound to the hydroxide precursor is 1.0-1.1, for example, 1.0, 1.02, 1.03, 1.04, 1.05, 1.06, 1.07, 1.08, 1.09, 1.1; the mass ratio of the co-solvent to the hydroxide precursor is 0.2-3, for example, 0.2, 0.5, 1.0, 1.5, 2.0, 2.5, 3.0; but it is not limited to the listed values, and other values ​​not listed within the above numerical range are also applicable.

[0013] By adopting the above scheme, in order to ensure that the lithium source and the nickel-cobalt-manganese source are fully sintered and grow into a material with a lithium ratio greater than 1 in the ternary material, the feed ratio of the lithium salt compound to the hydroxide precursor is set to be greater than 1, but at the same time, excessive lithium will also remain on the surface of the material to form residual alkali, which is not conducive to electrical properties. Therefore, the feed ratio of the lithium salt compound to the hydroxide precursor is set to be less than 1.1;

[0014] The use of co-solvents can improve the melting state, make the hydroxide precursor and lithium salt compound present a better melting state, and reduce the sintering temperature. If too much co-solvent is added, it will affect the proportion of active substances in the hydroxide precursor. If too little is added, the effect of the melting state cannot be achieved. In the later stage, the sintering temperature needs to be increased to achieve better melting and then form a crystal nucleus.

[0015] An optional solution is that in S1, the conditions of the first sintering are set to: when the oxygen content is set to above 80%, the temperature is increased to 800-1000°C, for example, 800°C, 830°C, 860°C, 900°C, 920°C, 950°C, 970°C, 1000°C, at a rate of 2-10°C / min, for example, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, 10°C / min, and the sintering is performed for 8-24h, for example, 8h, 9h, 12h, 16h, 19h, 24h; but it is not limited to the listed values, and other values ​​not listed within the above numerical range are also applicable.

[0016] An optional solution is that in S2, the mass ratio of the sintering material used in the second sintering to the surfactant is 100:0.1 to 100:0.3, for example, 100:0.1, 100:0.15, 100:0.20, 100:0.25, 100:0.3; but it is not limited to the listed values, and other unlisted values ​​within the above numerical range are also applicable.

[0017] By adopting the above technical solution, the surfactant can improve particle dispersion and control the coating uniformity of high-nickel ternary materials.

[0018] An optional solution is that, in S2, before the mixture of the sintering material and the surfactant is subjected to the second sintering, stirring, aging, filtering and washing are performed in sequence.

[0019] An optional solution is that in S2, the conditions for the second sintering are set to: when the oxygen content is set to above 80%, the temperature is increased to 600-900°C, for example, 600°C, 630°C, 650°C, 720°C, 760°C, 800°C, 850°C, 900°C, at a rate of 2-10°C / min, for example, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, 10°C / min, and the sintering is performed for 8-24h, for example, 8h, 9h, 12h, 16h, 19h, 24h; but it is not limited to the listed values, and other values ​​not listed within the above numerical range are also applicable.

[0020] An optional solution is that in S2, the chemical formula of the high nickel ternary material is LiNi x CoyMn 1-x-y O2, where 0.8≤x≤0.95, 0.01≤y<0.05.

[0021] An optional solution is that in S3, the reaction conditions are: the temperature is set to 100°C-300°C, for example, 100°C, 120°C, 150°C, 180°C, 220°C, 250°C, 280°C, 300°C, etc.; the pulse time is 0.1s-20s, for example, 0.1s, 0.5s, 1s, 5s, 8s, 12s, 15s, 18s, 20s, etc.; the number of pulses is 1-20 times, for example, 1 time, 2 times, 6 times, 10 times, 14 times, 18 times, 20 times, etc., but is not limited to the listed values, and other values ​​not listed within the above numerical range are also applicable.

[0022] An optional solution is that the introducing one or more sediments into the reaction chamber comprises:

[0023] Passing an iron source as a first reactant into the reaction chamber so that the iron source is adsorbed on the surface of the high-nickel ternary material;

[0024] Passing phosphate as a second reactant into the reaction chamber, so that the phosphorus source reacts with the iron source adsorbed on the surface of the high-nickel ternary material to generate a layer of iron phosphate;

[0025] A lithium source is introduced into the reaction chamber as the third reactant to form lithium iron phosphate.

[0026] In a second aspect, the present application also provides a composite electrode material prepared using the method described.

[0027] In a third aspect, the present application provides a lithium-ion battery, comprising a positive electrode and a negative electrode, wherein the material of the positive electrode is the composite electrode material.

[0028] In a fourth aspect, the present application also provides a vehicle, comprising the composite electrode material or lithium-ion battery.

[0029] Beneficial effects:

[0030] In the present application, atomic layer coating (ALD) technology is used to solve the problem of solid phase coating uniformity in the prior art. Atomic layer coating technology is a thin film deposition technology. By alternately introducing different gases, the thin film is grown layer by layer on the substrate. This technology has the ability to accurately control the thickness and composition of the thin film, and can achieve uniform coating at the atomic level. Therefore, in the present application, when preparing the composite electrode material, the high-nickel ternary material is placed in the reaction chamber of the atomic layer deposition equipment, and then one or more sediments are grown. After chemical adsorption and chemical reaction on the surface of the high-nickel ternary material, a composite electrode material with a coating layer is obtained. During the coating process, by precisely controlling the reaction conditions, uniform coating at the atomic level can be achieved, and the coating thickness can be controlled at the nm level. This feature avoids the reduction of gram capacity, while at the same time can well improve interface protection and improve long cycle performance, effectively solving the problem of poor uniformity of solid phase coating, and utilizing the characteristics of atomic layer deposition technology, an extremely thin coating thickness can be achieved, which is only 1 / 100 of that of solid phase coating.

[0031] Lithium iron phosphate is the cathode material with the highest market share. Due to its chemical composition, it starts to decompose at 500-600℃ and has the best thermal stability. At the same time, due to its olivine structure, the complete release of lithium ions will not cause damage to the olivine structure. At 100% SOC, Fe 3+ The oxidizing property is not strong and it is difficult to react with the electrolyte, so the thermal stability and long cycle performance of lithium iron phosphate (LFP) are high; in the present application, lithium iron phosphate material is selected as the coating agent of the high nickel ternary material, and a uniform iron-lithium coating layer is formed on the surface of the high nickel ternary material. Lithium iron phosphate is used as a coating agent to reduce the contact area between the electrode material and the electrolyte, slow down the corrosion of the electrolyte on the electrode material during the cycle, inhibit the occurrence of adverse interface reactions, and effectively improve the electrochemical performance of lithium-ion batteries; therefore, in the present application, the material advantages of high nickel ternary material and lithium iron phosphate are combined to prepare a composite electrode material. Under high SOC (state of charge), the surface structure of the composite electrode material is stable, which can delay the thermal runaway time and reduce the growth of high temperature storage and high temperature cycle DCR (direct current resistance), thereby achieving the purpose of taking into account energy density, thermal stability, excellent high temperature storage performance and long cycle. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the conventional technology, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0033] Figure 1 Schematic diagram of the steps of the method for preparing the composite electrode material in the embodiment of the present application. DETAILED DESCRIPTION

[0034] To make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the embodiments of the present application will be described in detail below in conjunction with the accompanying drawings. However, it will be appreciated by those skilled in the art that in the embodiments of the present application, many technical details are proposed in order to enable the reader to better understand the present application. However, even without these technical details and various changes and modifications based on the following embodiments, the technical scheme claimed in the present application can also be implemented. The division of the following embodiments is for the convenience of description, and the specific implementation of the present application should not be construed as any limitation, and the various embodiments can be combined with each other and quoted from each other without contradiction.

[0035] Reference below Figure 1 The preparation method of the composite electrode material of the embodiment of the present application is described in detail. According to the embodiment of the present application, the method comprises:

[0036] Step S1: mixing a hydroxide precursor, a lithium salt compound and a solvent, and performing a first sintering, crushing and classification to obtain a sintered material;

[0037] In this embodiment, it should be noted that the hydroxide precursor such as Ni hydroxide 0.9 Co 0.03 Mn 0.07 (OH)2 is mixed with a lithium salt compound such as lithium hydroxide in a certain ratio such as 1:1.05, and a solvent such as Na2O is added for full physical mixing. After being evenly mixed, it is placed in a box furnace for the first sintering, and naturally cooled after sintering. After cooling, it is crushed by jaws, crushed by rollers, and air flow crushed, and sintered after classification. The conditions for the first sintering are set as follows: oxygen is passed through the box furnace, the oxygen content is above 80%, and the temperature is raised to 800-1000°C at a rate of 2-10°C / min, and sintered for 8-24h.

[0038] Preferably, when the first sintering is carried out in a box furnace, the temperature is first increased slowly to a sintering temperature of 550°C at a heating rate of 5°C / min, and the temperature is maintained for 10 hours for the first stage of sintering; then the temperature is slowly increased to a sintering temperature of 870°C at a heating rate of 5°C / min, and the temperature is maintained for 12 hours for the second stage of sintering; pre-sintering is carried out in the first stage of sintering to burn out carbonate and hydroxyl groups in the hydroxide precursor and the lithium salt compound; then, in the second stage of sintering, the sintering temperature is increased to burn the hydroxide precursor and the lithium salt compound into a molten state, which is convenient for forming a crystal nucleus.

[0039] In some embodiments, the lithium salt compound is selected from one or more of lithium carbonate, lithium hydroxide and lithium nitrate; the co-solvent is selected from one or more of Li2CO3, LiOH, Li2O, LiF, LiCl, NaCl, NaF, Na2O, NaBO2, Na2BO3, SrO, Na2SO4, K2SO4, KCl, KF and B2O3.

[0040] Step S2: mixing the sintered material with a surfactant, and performing a second sintering and crushing to obtain a high-nickel ternary material;

[0041] In this embodiment, it should be noted that after the sintering material and the surfactant obtained in step S1 are stirred and mixed evenly in a certain ratio such as 100:0.2, the mixed solution is added to the reactor, and after stirring for 2 hours, aging for 3 hours, filtering, washing, and then placed in a box furnace for the second sintering, naturally cooled after sintering, and after cooling, jaw crushing, roller crushing, air flow crushing, and classification to obtain a high-nickel ternary material. Among them, the conditions for the second sintering are set as: oxygen is passed through the box furnace, the oxygen content is above 80%, and the temperature is raised to 600-900℃ at a rate of 2-10℃ / min, and sintered for 8-24h.

[0042] Preferably, when the second sintering is carried out in a box furnace, the first stage sintering is carried out at a heating rate of 5°C / min, a sintering temperature of 450°C, and a holding time of 10 hours; and then the second stage sintering is carried out at a heating rate of 5°C / min, a sintering temperature of 700°C, and a holding time of 12 hours; similarly, in the first stage sintering, the solid is pre-sintered to burn out impurities such as gas therein.

[0043] Step S3: placing the high-nickel ternary material into a reaction chamber of an atomic layer deposition device, setting the reaction conditions of the reaction chamber, introducing one or more sediments into the reaction chamber and applying the reaction conditions to obtain a composite electrode material coated with lithium iron phosphate.

[0044] In this embodiment, it should be noted that the high-nickel ternary material obtained in step S2 is placed in the reaction chamber of the atomic layer deposition equipment, and the reaction conditions of the reaction chamber are set, and then one or more sediments are introduced into the reaction chamber and the corresponding reaction conditions are applied. After chemical adsorption and chemical reaction on the surface of the high-nickel ternary material, a composite electrode material coated with lithium iron phosphate is obtained; wherein the reaction conditions of the reaction chamber are set to: temperature of 100°C-300°C; pulse time of 0.1s-20s; pulse number of 1-20 times. Sediments include phosphates (LATP, AlPO4, TiPO4, LixAlPO4), nitrogen-containing compounds (TiN, LiPON), fluorides (AlF3), oxides (Al2O3, ZrO, TiO2, MgO), lithium-containing compounds (Li x Ti y O z ,Li x B y O z ,Li x Al y O z ) and other compounds.

[0045] In one achievable manner, introducing one or more sediments into the reaction chamber specifically includes:

[0046] First, an iron source such as ferrocene (Fe(C5H5)2) is introduced into the reaction chamber as the first reactant with a pulse time of 2s, so that Fe(C5H5)2 is adsorbed on the surface of the high-nickel ternary material; then, a phosphate such as trimethyl phosphate (C3H9O4P) is introduced into the reaction chamber as the second reactant with a pulse time of 8s, so that the P source reacts with Fe(C5H5)2 adsorbed on the surface of the material to generate a layer of iron phosphate (FePO4); finally, a lithium source such as lithium gas is introduced into the reaction chamber as the third reactant with a pulse time of 5s, so that the final deposit is lithium iron phosphate. The above is one cycle of atomic layer deposition. After repeating the atomic deposition cycle for several cycles, a composite electrode material with coated lithium iron phosphate is obtained.

[0047] The present application is described below with reference to specific embodiments. It should be noted that these embodiments are merely illustrative and do not limit the present application in any way.

[0048] Embodiment 1:

[0049] A method for preparing a high-nickel ternary material comprises the following process:

[0050] Step 1: Select the precursor Ni hydroxide 0.9 Co 0.03 Mn 0.07(OH)2 and lithium hydroxide are mixed with SrO in a ratio of 1:1.05, and then placed in a box furnace for the first sintering. Oxygen is passed through the box furnace, and the sintering program is set as follows: heating rate of 5℃ / min, sintering temperature of 550℃, holding time of 10h, and then heating rate of 5℃ / min, sintering temperature of 870℃, holding time of 12h, and then naturally cooled. After jaw crushing, roller crushing, air flow crushing, and classification, the sintering material is obtained.

[0051] Step 2: Stir the sintering material obtained in step 1, surfactant (PEG400) and deionized water in a ratio of 100:0.2:500 for 4 hours, add the mixed solution into the reactor, stir for 2 hours, age for 3 hours, filter and wash, and place in a box furnace for the second sintering. The box furnace is ventilated with oxygen, and the oxygen atmosphere is controlled at 85%. The sintering program is set as follows: heating rate of 5°C / min, sintering temperature of 450°C, holding time of 10 hours, and then continue to heat at a rate of 5°C / min, sintering temperature of 700°C, holding time of 12 hours, and then cool naturally. After jaw crushing, roller crushing, air flow crushing, and classification, high nickel ternary materials are obtained.

[0052] Embodiment 2:

[0053] A method for preparing a composite electrode material comprises the following process:

[0054] Step 1 and step 2 are the same as step 1 and step 2 in Example 1;

[0055] Step 3. Place the high-nickel ternary material prepared in step 2 into the reaction chamber of the atomic layer deposition equipment. The temperature of the reaction chamber is set to 260°C. First, ferrocene (Fe(C5H5)2) is introduced into the reaction chamber as the first reactant with a pulse time of 2s, so that Fe(C5H5)2 is adsorbed on the surface of the high-nickel ternary material. Then, trimethyl phosphate (C3H9O4P) is introduced into the reaction chamber as the second reactant with a pulse time of 8s, so that the P source reacts with Fe(C5H5)2 adsorbed on the surface of the material to generate a layer of iron phosphate (FePO4). Finally, lithium gas is introduced into the reaction chamber as the third reactant with a pulse time of 5s, so that the final deposit is lithium iron phosphate. This is one cycle of atomic layer deposition. Repeat the atomic deposition cycle for 10 cycles to obtain a composite electrode material coated with lithium iron phosphate.

[0056] Embodiment 3:

[0057] A method for preparing a composite electrode material comprises the following process:

[0058] Step 1 and step 2 are the same as step 1 and step 2 in Example 1;

[0059] Step 3. Place the high-nickel ternary material prepared in step 2 into the reaction chamber of the atomic layer deposition equipment. The temperature of the reaction chamber is set to 260°C. First, ferrocene (Fe(C5H5)2) is introduced into the reaction chamber as the first reactant with a pulse time of 2s, so that Fe(C5H5)2 is adsorbed on the surface of the high-nickel ternary material. Then, trimethyl phosphate (C3H9O4P) is introduced into the reaction chamber as the second reactant with a pulse time of 8s, so that the P source reacts with Fe(C5H5)2 adsorbed on the surface of the material to generate a layer of iron phosphate (FePO4). Finally, lithium gas is introduced into the reaction chamber as the third reactant with a pulse time of 5s, so that the final deposit is lithium iron phosphate. This is one cycle of atomic layer deposition. Repeat the atomic deposition cycle for 30 cycles to obtain a composite electrode material coated with lithium iron phosphate.

[0060] Embodiment 4:

[0061] A method for preparing a composite electrode material comprises the following process:

[0062] Step 1 and step 2 are the same as step 1 and step 2 in Example 1;

[0063] Step 3. Place the high-nickel ternary material prepared in step 2 into the reaction chamber of the atomic layer deposition equipment. The temperature of the reaction chamber is set to 260°C. First, ferrocene (Fe(C5H5)2) is introduced into the reaction chamber as the first reactant with a pulse time of 2s, so that Fe(C5H5)2 is adsorbed on the surface of the high-nickel ternary material. Then, trimethyl phosphate (C3H9O4P) is introduced into the reaction chamber as the second reactant with a pulse time of 8s, so that the P source reacts with Fe(C5H5)2 adsorbed on the surface of the material to generate a layer of iron phosphate (FePO4). Finally, lithium gas is introduced into the reaction chamber as the third reactant with a pulse time of 5s, so that the final deposit is lithium iron phosphate. This is one cycle of atomic layer deposition. Repeat the atomic deposition cycle for 50 cycles to obtain a composite electrode material coated with lithium iron phosphate.

[0064] Comparative Example 1

[0065] A preparation process of a high nickel ternary material of solid phase coated lithium iron phosphate is as follows:

[0066] Step 1 and step 2 are the same as step 1 and step 2 of embodiment 1;

[0067] Step 3: Place the high-nickel ternary material, nano-scale lithium iron phosphate, in a box furnace for sintering. The sintering program is set as follows: heating rate of 5°C / min, sintering temperature of 700°C, and holding time of 10h to obtain a high-nickel ternary material of solid-phase coated lithium iron phosphate.

[0068] Lithium-ion battery preparation:

[0069] The method for making a secondary lithium-ion battery using the high-nickel ternary material prepared in Examples 1 to 4 of the present application and Comparative Example 1 is as follows:

[0070] The positive electrode ternary material, the conductive agent (SP), and the binder polyvinylidene fluoride (PVDF) are added to N-methylpyrrolidone (NMP) in a weight ratio of 95:2:3, and are fully mixed and stirred to form a uniform slurry with a solid content of 65%. The slurry is coated on an aluminum foil current collector, dried, and pressed into a pole piece;

[0071] Add the negative electrode artificial graphite, conductive carbon black (SP), carboxymethyl cellulose (CMC), and adhesive (SBR) in a weight ratio of 96:0.8:1.2:2 into sufficient pure water, stir to form a uniform slurry, apply it on the copper foil current collector, dry and press into a pole piece;

[0072] The diaphragm is made of PP (polypropylene) / PE (polyethylene) composite film material. The pressed positive and negative electrode sheets are spot welded to the upper ears. After inserting the diaphragm, they are wound on the winder and loaded into the soft package fixture. The top and side are sealed, and then placed in an oven for baking. After that, 15g of electrolyte is injected in an environment with a relative humidity of less than 1.5%. The electrolyte uses a mixed solvent with a mass ratio of EC (ethylene carbonate): DEC (diethyl carbonate): DMC (dimethyl carbonate) = 1:1:1. The electrolyte is 1M lithium hexafluorophosphate. The liquid is injected and vacuum sealed after 24 hours of formation.

[0073] Testing and analysis

[0074] Under the same conditions, the batteries prepared in the above Examples 1-4 and Comparative Example 1 were subjected to charge and discharge tests. The specific test methods are as follows:

[0075] Charge and discharge performance test: According to the test method of GB / T18287-2000, specifically, in a constant temperature room at 25℃±5℃, charge at a constant current of 0.33C to an upper limit voltage of 4.25V, then change to constant voltage charging. When the charging current is less than or equal to 0.05C, the charging is stopped when the longest charging time is no more than 8h. After charging, place it at a temperature of 25℃±5℃ for 0.5h-1h, discharge at a current of 0.33C to a termination voltage of 2.8V, and record the discharge capacity as the retention capacity Cn1.

[0076] Initial DCR (Direct Current Resistance) refers to the DCR before cycling. The steps are to first charge and discharge the fresh battery at 0.33C in the voltage range of 2.8-4.25V to a fixed capacity, with a discharge capacity of Cn2, and then discharge at 0.33C current, with the end condition being 0.5Cn2, recording the voltage as V1, discharging at 4C for 10S, and recording the voltage at this time as V2, then the initial DCR = (V2-V1) / 4C. Cycle 1000ClsΔDCR (%) refers to the battery after 1000 cycles with the same initial DCR steps, and the measured DCR is DCR2, then ΔDCR (%) = (DCR2-initial DCR) / initial DCR*100%.

[0077] The cycle 1000Cls retention rate means that the fresh battery is first charged and discharged at 1C in the voltage range of 2.8-4.25V, the discharge capacity of the first cycle is Cn3, and then the discharge capacity of the 1000th cycle is Cn4, Cn4 / Cn3*100% is the cycle 1000Cls retention rate.

[0078] Powder impedance test: The powder impedance test of the composite electrode material was carried out using a PR510 powder resistance test system, with a sample weight of 1 g, a pressure of 10,000 N, and a holding time of 30 s.

[0079] As shown in Table 1, compared with Example 1, the powder impedances of Examples 2, 3, and 4 increase successively, and the gram capacity decreases successively, which indicates that the lithium iron phosphate material has been successfully deposited on the surface of the high-nickel ternary material. Since the electronic conductivity and lithium ion diffusion coefficient of the lithium iron phosphate material are smaller than those of the ternary material, the powder impedance will increase successively, and the gram capacity will decrease successively; compared with Example 1, the powder impedance of Comparative Example 1 increases the most, and the gram capacity decreases a lot, indicating that the solid phase coating amount is uncontrollable, affecting the gram capacity.

[0080] As shown in Table 1, compared with Example 1, the cycle DCR growth of Examples 2, 3, and 4 is successively reduced, and the cycle retention rate is successively increased, but the improvement effect of Example 3 and Example 4 tends to be the same. This shows that the lithium iron phosphate material has been successfully deposited on the surface of the high-nickel ternary material. The structural stability and interface stability of the lithium iron phosphate material help the composite material to resist the collapse of the ternary structure during the charge and discharge process, and the risks of large DCR growth and low cycle retention rate caused by the interface side reaction. In addition, compared with Example 3 and 4, the gram capacity sacrifices 2.5mAh / g, but the cycle DCR growth and cycle retention rate do not benefit much, indicating that the deposition thickness of Example 3 has met the performance requirements for improving the cycle process, which is the most balanced improvement condition. Compared with Example 1, the DCR growth of Comparative Example 1 is still improved, and the retention rate is also improved, but relative to Examples 2, 3 and 4, the improvement of the cycle DCR growth and the cycle retention rate is not obvious, indicating that the solid phase sintering still has uneven coating, the thickness is uncontrollable, the coated place is unfavorable for lithium ion transmission, affecting the gram capacity, and the uncoated place has many interface side reactions, affecting the cycle and DCR growth.

[0081] Table 1

[0082]

[0083] In summary, the modified high-nickel ternary material of this embodiment has lithium iron phosphate deposited on the surface, which is thin and uniform, and can provide capacity while improving the material interface, avoiding too much capacity reduction due to the presence of the coating; the chemical composition of lithium iron phosphate is stable, and it can only be decomposed above 500°C, and has the best thermal stability. In addition, due to its unique olivine structure, lithium iron phosphate has a stable structure and is very resistant to overcharging. Fe 3+ The oxidizing property is not strong and the interface can be well protected, so depositing an appropriate amount of lithium iron phosphate can effectively improve the long-term cycle performance.

[0084] It should be understood that the above specific embodiments of the present application are only used to illustrate or explain the principles of the present application, and do not constitute a limitation to the present application. Therefore, any modifications, equivalent substitutions, improvements, etc. made without departing from the spirit and scope of the present application should be included in the protection scope of the present application. In addition, the claims attached to the present application are intended to cover all changes and modifications that fall within the scope and boundaries of the attached claims or the equivalent forms of such scope and boundaries.

Claims

1. A method for preparing a composite electrode material, characterized in that: The steps include: S1: mixing a hydroxide precursor, a lithium salt compound and a solvent, and performing a first sintering, crushing and classification to obtain a sintering material; S2: mixing the sintered material with a surfactant, and performing a second sintering and crushing to obtain a high-nickel ternary material; S3 places the high-nickel ternary material into a reaction chamber of an atomic layer deposition device, sets the reaction conditions of the reaction chamber, introduces one or more sediments into the reaction chamber and applies the reaction conditions to obtain a composite electrode material coated with lithium iron phosphate.

2. The method according to claim 1, characterized in that In said S1, The mass ratio of the lithium salt compound to the hydroxide precursor is 1.0-1.1; The mass ratio of the co-solvent to the hydroxide precursor is 0.2-3.

3. The method according to claim 1, characterized in that In said S1, The first sintering conditions are set as follows: when the oxygen content is set to be above 80%, the temperature is raised to 800-1000° C. at a rate of 2-10° C. / min, and the sintering is performed for 8-24 hours.

4. The method according to claim 1, characterized in that: In said S2, The mass ratio of the sintering material used in the second sintering to the surfactant is 100:0.1 to 100:0.

3.

5. The method according to claim 1, characterized in that In said S2, Before the second sintering of the mixture of the sintering material and the surfactant, stirring, aging, filtering and washing are performed in sequence; and / or, The second sintering conditions are set as follows: when the oxygen content is set to be above 80%, the temperature is raised to 600-900° C. at a rate of 2-10° C. / min, and the sintering is performed for 8-24 hours.

6. The method according to claim 1, characterized in that In said S2, The general chemical formula of the high nickel ternary material is LiNi x CoyMn 1-x-y O2, where 0.8≤x≤0.95, 0.01≤y<0.

05.

7. The method according to claim 1, characterized in that In said S3, The reaction conditions are: the temperature is set at 100°C-300°C; the pulse time is 0.1s-20s; the number of pulses is 1-20 times; and / or, The introducing one or more sediments into the reaction chamber comprises: Passing an iron source as a first reactant into the reaction chamber so that the iron source is adsorbed on the surface of the high-nickel ternary material; Passing phosphate as a second reactant into the reaction chamber, so that the phosphorus source reacts with the iron source adsorbed on the surface of the high-nickel ternary material to generate a layer of iron phosphate; A lithium source is introduced into the reaction chamber as the third reactant to form lithium iron phosphate.

8. A composite electrode material, characterized in that: The method is prepared by any one of claims 1 to 7.

9. A lithium ion battery, characterized in that: It comprises a positive electrode and a negative electrode, and the material of the positive electrode is the composite electrode material as claimed in claim 8.

10. A vehicle, characterized in that: Comprising the composite electrode material according to claim 8 or the lithium ion battery according to claim 9.

Citation Information

Patent Citations

  • High-nickel ternary positive electrode material coated with lithium iron phosphate nano-powder and preparation method thereof, and applications

    CN110233249A

  • Method for preparing nickel-cobalt lithium manganate monocrystal cathode material by doping strontium

    CN110867580A

  • Positive electrode material coated with phosphorus-containing compound and preparation method of positive electrode material

    CN111509209A

  • Manufacturing method of high-compaction lithium battery positive electrode material nickel cobalt lithium manganate

    CN111710843A

  • Lithium-rich manganese-based positive electrode material and preparation method thereof

    CN118315561A

Cited By

  • Composite positive electrode material, preparation method thereof and battery

    CN121149223A